Revision of the Apocephalus mucronatus group of ant decapitating flies (Diptera: Phoridae) - Brown, Brian V. (Zootaxa, 2012)
The species of the New World genus Apocephalus are parasitoids, mostly of ants, and many undescribed species exist. Here, the Apocephalus mucronatus group species are revised, with five new to science described: A. longimanus, A. longimucrus, A. missouriensis, A. setissitergus, and A. weissi. Along with the previously known two species, Apocephalus mucronatus Borgmeier and Apocephalus mesacanthus Brown & Lebrun, these form a well-defined monophyletic group based on the presence of a spinelike protrusion on the oviscape, distinctly sclerotized posterolateral membrane on intersegment 7–8, and other female characters. Life history data are known for only one species, which is a parasitoid of Camponotus carpenter ants.